Pengaruh Terapi Puzzle terhadap Peningkatan Fungsi Kognitif Pada Pasien Stroke Iskemik di RS Islam Jakarta Pondok Kopi - Selviyanti, Fenty; Khamid, Abdul (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT According to data from the World Stroke Organization, the prevalence of stroke every year is 13.7 million new cases of stroke, and around 5.5 million deaths occur due to stroke. The prevalence of stroke in Indonesia according to the 2023 Indonesian Health Survey is 8.7%. Meanwhile, in DKI Jakarta, the prevalence of stroke based on diagnosis in residents aged ≥ 15 years is 13.5%. The most common type of stroke is ischemic stroke with a prevalence reaching 87% of stroke events. Stroke sufferers will experience the impact of cognitive impairment. One technique or therapy that can be used for stroke sufferers with cognitive impairment is puzzle installation training. To determine the effect of puzzle therapy on improving cognitive function in ischemic stroke patients. Quasy experiments use a one group pretest-posttest design, which does not use a control group. The sampling technique uses Random Sampling. The frequency distribution of cognitive dysfunction before being given puzzle therapy was that most respondents had mild cognitive dysfunction (89.1%) and afterward did not experience cognitive dysfunction (65.5%). There is an effect of puzzle therapy on improving cognitive function in ischemic stroke patients with a p value of 0.000 < α (0.05), which means there is a significant difference in the average value between before and after being given puzzle therapy.= There is an effect of puzzle therapy on improving cognitive function in ischemic stroke patients. It is hoped that nurses can help ischemic stroke patients maintain their memory by using puzzle therapy which can help improve cognitive function. Keywords: Puzzle Therapy, Ischemic Stroke, Cognitive Function  ABSTRAK Menurut data World Stroke Organization prevalensi stroke setiap tahunnya sebesar 13,7 juta kasus baru stroke, dan sekitar 5,5 juta kematian terjadi akibat penyakit stroke. Prevalensi penyakit stroke di Indonesia menurut Survei Kesehatan Indonesia tahun 2023 sebesar 8,7%. Sedangkan di DKI Jakarta prevalensi penyakit stroke berdasarakan diagnosis pada penduduk umur ≥ 15 tahun sebesar 13,5%. Jenis stroke yang paling sering terjadi adalah stroke iskemik dengan prevalensi mencapai 87% dari kejadian stroke. Penderita stroke akan mengalami dampak dari adanya gangguan kognitif. Salah satu tehnik atau terapi yang dapat dilakukan kepada penderita stroke dengan gangguan kognitif adalah dengan pelatihan pemasangan puzzle. Mengetahui pengaruh terapi puzzle terhadap peningkatan fungsi kongnitif pada pasien stroke iskemik. Quasy eksperimen menggunakan rancangan one group pretest-posttest design, yang tidak menggunakan kelompok kontrol. Teknik pengambilan sampel menggunakan Random Sampling. Distribusi frekuensi gangguan fungsi kognitif sebelum diberikan terapi puzzle sebagian besar responden dengan gangguan fungsi kognitif ringan (89,1%) dan sesudahnya tidak mengalami gangguan fungsi kognitif (65,5%). Ada pengaruh terapi puzzle terhadap peningkatan fungsi kongnitif pada pasien stroke iskemik dengan nilai p value 0,000 < α (0,05) yang berarti ada perbedaan nilai rata-rata yang signifikan antara sebelum dan sesudah diberikan terapi puzzle.Ada pengaruh terapi puzzle terhadap peningkatan fungsi kognitif pada pasien stroke iskemik. Diharapkan perawat dapat membantu pasien stroke iskemik dalam menjaga daya ingatnya dengan menggunakan terapi puzzle yang dapat membantu meningkatkan fungsi kognitif.         Kata Kunci: Terapi Puzzle, Stroke Iskemik, Fungsi Kognitif